PENGARUH KOMBINASI LIMBAH KULIT ARI KEDELAI DAN LIMBAH SISA MAKANAN TERHADAP PERTUMBUHAN DAN PRODUKTIVITAS MAGGOT BLACK SOLDIER FLY (Hermetia illucens) - Septyani, Fitria; Fitriyah, Fitriyah; Hasyim, Muhammad Asmuni (Prodi Biologi Universitas PGRI Ronggolawe, 2025)
The accumulation of organic waste in Indonesia is dominated by household waste, namely food waste and is also produced from household industries such as tempeh processing, namely soybean husk waste. One of the best solutions that can be done to minimize the accumulation of organic waste is to use Black Soldier Fly (Hermetia illucens) larvae. The organic waste will be consumed by BSF larvae and converted into nutrients for larval growth and development. The purpose of this study is to determine the effect of a combination of soybean husk waste and food waste on the growth and productivity of Black Soldier Fly (Hermetia illucens) larvae. This study is an experimental study of Complete Random Design (RAL) using 5 treatments, and 4 replicates, namely P1 (100% soybean husk waste), P2 (50% soybean husk waste + 50% food waste waste), P3 (75% soybean husk waste + 25% food waste waste), P4 (25% soybean husk waste + 75% food waste waste), P5 (100% food waste waste). The main parameters discussed in this study are larval growth including weight and length and larval productivity in the form of protein levels. The supporting parameters discussed are the Survival Rate and Waste Reduction Index values. Data analysis uses normality test, homogeneity test, ANOVA, and Duncan test at a confidence interval of 95%. The results showed that the combination of soybean husk waste and food waste had a significant effect (P<0.05) on larval growth and productivity. The best combination treatment that contributed to the development (length and weight) of BSF larvae was in the P3 treatment with the highest yields of 1.38cm and 0.17g respectively. In addition, the Survival Rate, Waste Reduction Index, and larval protein levels were the highest in the P1 treatment at 100%, 4.82%, and 13.07%, respectively.